2020
DOI: 10.1099/mgen.0.000321
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of carbapenemase-producing Enterobacteriaceae in Queensland reveals widespread transmission of bla IMP-4 on an IncHI2 plasmid

Abstract: Carbapenemase-producing Enterobacteriaceae (CPE) are an increasingly common cause of healthcare-associated infections and may occasionally be identified in patients without extensive healthcare exposure. bla IMP-4 is the most frequently detected carbapenemase gene in Enterobacteriaceae within Australia, but little is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 42 publications
6
21
0
Order By: Relevance
“…The ter-type 2 operons were located on the IncHI2 plasmids of E. coli strains, and were also found on the IncHI2 plasmids carried by Y. pseudotuberculosis and K. pneumoniae (Supplementary Figure 2), suggesting that this type of operon was horizontally transferred in E. coli as well as within the Enterobacteriaceae through plasmids. The conjugative IncHI2 plasmid is widely found in Enterobacteriaceae and is known to mediate various drug resistance genes (Herrera-León et al, 2011;Roberts et al, 2020). In fact, the plasmids found to harbor the ter-type 2 operons in this study carried three or more drug resistance genes (Figure 5).…”
Section: Discussionmentioning
confidence: 69%
“…The ter-type 2 operons were located on the IncHI2 plasmids of E. coli strains, and were also found on the IncHI2 plasmids carried by Y. pseudotuberculosis and K. pneumoniae (Supplementary Figure 2), suggesting that this type of operon was horizontally transferred in E. coli as well as within the Enterobacteriaceae through plasmids. The conjugative IncHI2 plasmid is widely found in Enterobacteriaceae and is known to mediate various drug resistance genes (Herrera-León et al, 2011;Roberts et al, 2020). In fact, the plasmids found to harbor the ter-type 2 operons in this study carried three or more drug resistance genes (Figure 5).…”
Section: Discussionmentioning
confidence: 69%
“…Because of the physical proximity of these ARGs and the presence of two bordering IS903 copies, the ARG locus-2 of pCM18-216 has the potential to facilitate the simultaneous horizontal gene transfer of the ESBL gene bla SHV-12 and the fluoroquinolone resistance gene qnr B2, along with other antimicrobial resistance genes, through a single transposition event. In Australia, bla IMP-4 genes have been associated with IncHI2 plasmids carried by E. hormaechei with various MLST profiles, but only two ST110 isolates [ 53 ]. These antimicrobials are considered of very high importance and their use in companion animals is not generally recommended ( https://vetantibiotics.fvas.unimelb.edu.au/ ).…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the bla NDM-5 -carrying IncHI2 plasmid are scarce. Previous reports have also suggested that the IncHI2 plasmid was considered to be an important vehicle in the spread of carbapenem resistance genes such as bla NDM-1 , bla NDM-4 , bla NDM-9 and bla IMP-4 among Enterobacteriaceae from human and animals [ 13 , 23 , 24 ]. Since the discovery of mcr-1 gene in 2015 that threatens the effectiveness of polymyxins, the IncHI2 plasmid that carried mcr-1 has been found in Enterobacteria from a variety of sources, including humans [ 25 ], animals (cattle, pigs, chickens, ducks and turkeys) [ 26 , 27 ], food (chicken, beef, pork, milk and vegetables) [ 28 , 29 ] and the environment (farm soil and wastewater) [ 30 ] in several countries around the world.…”
Section: Discussionmentioning
confidence: 99%